An exercise prescription for patients with lung cancer improves the quality of life, depression, and anxiety - Lei, Juntian; Yang, Jianyu; Dong, Lei; Xu, Jilai; Chen, Jing; Hou, Xiao; Bai, Zhenmin (Frontiers in Public Health, 2022)
Introduction Lung cancer has the highest rates of morbidity and mortality among all cancers. Patients with lung cancer inevitably confront psychosocial discomforts and progressively experience depression and anxiety that potentially impact the clinical outcomes [e.g., quality of life (QoL)]. These mental disorders in patients with lung cancer may effectively be alleviated with prescribed Chinese traditional mind-body exercises. This study aimed to determine the effect of the exercise prescription containing Chinese traditional mind-body exercise on QoL, depression, and anxiety in patients with lung cancer. Methods In this study, 52 patients with non-small cell lung cancer (NSCLC) recruited from the China-Japan Friendship Hospital were divided into two groups, namely, the experimental group (N = 26) and the control group (N = 26). The experimental group was treated with an 8-week exercise prescription containing aerobic and resistance training. The control group received the usual care during the study period. The QoL, depression, and anxiety were separately investigated using EORTC QLQ-C30, EORTC QLQ-LC13, the Self-Rating Depression Scale (SDS), and the Self-Rating Anxiety Scale (SAS) at baseline and post-intervention. The scores of questionnaires were analyzed using the paired sample and independent sample t-tests to explore the intragroup and intergroup differences, respectively. Results The EORTC QLQ-C30 scores for physical functioning, role functioning, emotional functioning, and global QoL in the experimental group at post-intervention were significantly higher than those at baseline. The EORTC QLQ-C30 scores for fatigue, pain, dyspnea, and insomnia in the experimental group at post-intervention were significantly lower than those at the baseline. The SDS scores (baseline: 57.74 ± 8.77 vs. post-intervention: 51.42 ± 7.31, p < 0.05) and the SAS scores (baseline: 56.63 ± 9.39 vs. post-intervention: 49.16 ± 7.83, p < 0.05) in the experimental group at post-intervention were significantly lower than those at baseline. Conclusions The 8-week exercise prescription containing moderate-intensity Baduanjin (5 days per week) can effectively alleviate QoL, depression, and anxiety in patients with NSCLC. Our exercise prescription is an effective supportive treatment for lung cancer patients with depression and anxiety. Clinical trial registration Chinese Clinical Trial Registry (ChiCTR1900025121).